CryoEM of RUVBL1–RUVBL2–ZNHIT2, a complex that interacts with pre-mRNA-processing-splicing factor 8. Issue 2 (24th December 2021) - Serna, Marina; González-Corpas, Ana; Cabezudo, Sofía; López-Perrote, Andrés; Degliesposti, Gianluca; Zarzuela, Eduardo; Skehel, J Mark; Muñoz, Javier; Llorca, Oscar
Abstract: Biogenesis of the U5 small nuclear ribonucleoprotein (snRNP) is an essential and highly regulated process. In particular, PRPF8, one of U5 snRNP main components, requires HSP90 working in concert with R2TP, a cochaperone complex containing RUVBL1 and RUVBL2 AAA-ATPases, and additional factors that are still poorly characterized. Here, we use biochemistry, interaction mapping, mass spectrometry and cryoEM to study the role of ZNHIT2 in the regulation of the R2TP chaperone during the biogenesis of PRPF8. ZNHIT2 forms a complex with R2TP which depends exclusively on the direct interaction of ZNHIT2 with the RUVBL1–RUVBL2 ATPases. The cryoEM analysis of this complex reveals that ZNHIT2 alters the conformation and nucleotide state of RUVBL1–RUVBL2, affecting its ATPase activity. We characterized the interactions between R2TP, PRPF8, ZNHIT2, ECD and AAR2 proteins. Interestingly, PRPF8 makes a direct interaction with R2TP and this complex can incorporate ZNHIT2 and other proteins involved in the biogenesis of PRPF8 such as ECD and AAR2. Together, these results show that ZNHIT2 participates in the assembly of the U5 snRNP as part of a network of contacts between assembly factors required for PRPF8 biogenesis and the R2TP-HSP90 chaperone, while concomitantly regulating the structure and nucleotide state of R2TP.